Prognostic biomarkers for chemotherapy response on hpe in osteosarcoma patients - Ahmed, Farahat Nadeem (2021)
Osteosarcoma is the most common primary malignant tumour derived from primitive bone-forming mesenchymal tissue. The study aims to find any association between clinical findings, tumour growth patterns, tumour volume, pulmonary metastasis, and tumour necrosis with chemotherapy response on HPE in osteosarcoma patients following neoadjuvant chemotherapy which in tern correlates with the patient survival. These prognostic factors may help in the application of risk adaptive management of osteosarcoma patients. This is a retrospective cohort study of all patients treated between January 2000 and December 2020. MR images of patients with osteosarcoma were taken from PACS and data analysed for the study variables as described. Patients were divided into three groups based on the tumour growth pattern, namely concentric, eccentric, and longitudinal groups. Tumour volume and tumour necrotic volumes were calculated using reliable semi-automated software. Correlations between tumour growth patterns, volumes and clinical features with histopathological variables were analysed. We included 18 patients with an age range of 6–48 years (median = 20). In total, 5 patients had a good chemotherapy response. Lung metastasis and pathological fractures were found in 7 patients. In our study, a smaller necrotic volume calculated on pre-chemotherapy MRI showed a significant response to chemotherapy in terms of histological necrosis. There was a significant correlation found in the chemotherapy response for variables like pathological fractures and location of the tumour. However, there was no significant correlation found between chemotherapy response and the other variables like age, gender, subtype, presence of lung metastasis, growth pattern and tumour volume. Overall, the study suggests that growth patterns, tumour volume and clinical features like the presence of pulmonary metastasis in imaging were not associated with the HPE necrosis outcome. However, there is evidence to suggest that patients with a comparatively smaller pre-chemotherapy tumour necrotic volume showed a good chemotherapy response. Also, the absence of pathological fracture showed a good chemotherapy response.